インプラント体の表面性状の違いが周囲骨吸収に及ぼす影響：埋入後5 年経過時の同一患者の隣接するインプラント体による比較 - 藤澤, 健司; 安陪, 晋; 大江, 剛; 永井, 宏和; 宮本, 洋二 (Journal of Japanese Society of Oral Implantology, 2015)
To investigate whether the surface topography of dental implants affects bone loss around the implants, we installed Brånemark implants with two different surface roughnesses : a smooth machined surface and a rough surface created by anodic oxidation, on an adjacent area in identical patients, and examined marginal bone level radiographically. The study sample consisted of 21 patients (14 men and 7 women). Sixty implants were installed, 30 with a smooth surface and 30 with a rough surface. Thirty-six implants were submerged, and 24 implants were placed for immediate loading. The marginal bone level was radiographically examined at implant installation, and at 1, 3 and 5 years after installation. The Wilcoxon signedrank test was used to test the significance of marginal bone loss of each surface group. The difference between the two implant surfaces in marginal bone loss was not statistically significant at 1 year (p=0.796), 3 years (p=0.357) and 5 years (p=0.518) in the submerged group, nor at 1 year (p=0.180), 3 years (p=0.357) and 5 years (p=0.172) in the immediately loaded group. However, there were some cases with large bone loss in rough surfaces associated with peri-implantitis.